2017
DOI: 10.1038/srep42717
|View full text |Cite
|
Sign up to set email alerts
|

SwissADME: a free web tool to evaluate pharmacokinetics, drug-likeness and medicinal chemistry friendliness of small molecules

Abstract: To be effective as a drug, a potent molecule must reach its target in the body in sufficient concentration, and stay there in a bioactive form long enough for the expected biologic events to occur. Drug development involves assessment of absorption, distribution, metabolism and excretion (ADME) increasingly earlier in the discovery process, at a stage when considered compounds are numerous but access to the physical samples is limited. In that context, computer models constitute valid alternatives to experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
7,160
0
77

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 10,800 publications
(7,284 citation statements)
references
References 78 publications
47
7,160
0
77
Order By: Relevance
“…The protein and ligand were docked with iGEMDOCK and Autodock Vina [24], the results were retrieved on the basis of energy values, Van der Waals force, binding affinity between protein and ligand. The SAR molecules were generated with the help of SWISS ADME [25][26][27] online tool. In a study by Jeyam et al showed that a good interaction between 1,3 β glucan synthase with 20 phytoconstituents and the inhibition of 1,3 β glucan synthase was better than echinocandins [28].…”
Section: Discussionmentioning
confidence: 99%
“…The protein and ligand were docked with iGEMDOCK and Autodock Vina [24], the results were retrieved on the basis of energy values, Van der Waals force, binding affinity between protein and ligand. The SAR molecules were generated with the help of SWISS ADME [25][26][27] online tool. In a study by Jeyam et al showed that a good interaction between 1,3 β glucan synthase with 20 phytoconstituents and the inhibition of 1,3 β glucan synthase was better than echinocandins [28].…”
Section: Discussionmentioning
confidence: 99%
“…Saat ini, basis data SwissADME (http://www. swissadme.ch/) yang dapat diakses secara publik untuk membantu relatif lebih mudah pemilihan senyawa yang memili "The Rule of Five" (Daina et al, 2017). Disisi lain, prediksi parameter farmakokinetik juga dapat dilakukan pada bidang veteriner sebagai tahap awal untuk uji pra-klinis bagi obat-obatan (Mahmood, 2007).…”
Section: Prediksi Parameter Farmakokinetikunclassified
“…For the compounds considered in this study we use the following computational tools: (i) SwissADME [14] and FAFDrugs [15,16] to assess their pharmacokinetics and to predict their ADME-Tox profiles, (ii) PASS online [17] for envisaging their toxic/side effects, (iii) CarcinoPred-EL [18] to predict carcinogenicity, Pred-hERG4.0 [19] to assess cardiotoxicity and ENDOCRINE DISRUPTOME [20] to evaluate their endocrine disruption potential. These tools have been selected among the numerous computational utilities destined to predict the ADME-Tox profile and pharmacokinetics because of their continuous update, accessibility by free-login on the websites and of their robustness, accompanied by easy inputs and interpretations.…”
Section: Methodsologymentioning
confidence: 99%